What is maaf for in the Indonesian language? A study of its use in written sources - Siti Sumarti; Wening Sahayu; Sulis Triyono (Studies in English Language and Education, 2020)
Apologizing, commonly, contains the word ‘sorry’ for the English language and other languages, has the meaning of ‘feeling regret or penitence’. In the Indonesian language, ‘sorry’ is similar to the word ‘maaf’. The study focuses on the use of ‘maaf’ in the Indonesian language. Its primary aim is to find out the functions of ‘maaf’ in the Indonesian language. The subject of this study is written data which is from three Indonesian novels. Meanwhile, the object is the functions of the use of the word ‘maaf’. Reading attentively method was used in collecting data specifically in noting technique. The technique used for data analysis is pragmatic (identity) method. The researchers used the framework by Kimura (1994) combined with Pratiwi and Hilaliyah (2018) in analyzing the functions of ‘maaf’ in the Indonesian language. Based on the analysis, it was found that the function of ‘maaf’ in the Indonesian language are for regret (63 occurrences) as the most used in the novels, followed by attention-getter (five occurrences), closing (four occurrences), request (three occurrences), and mocking or teasing (two occurrences ) as the least used function. Generally, the characters in the novel were displayed to produce apologies in different ways, depending on power (i.e. employee to employer), relationships (i.e. a nephew to his aunt, between friends), age (i.e. same age, young to old, and vice-versa) and situation (i.e. approaching strangers). These different ways bear various functions of ‘maaf’ in their conversations. The article further elaborates on the results and provides recommendations for future research in related studies.